TOWARDS QUALITY PESANTREN AND MADRASAH IN GLOBAL ERA - Busahdiar, Busahdiar (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2017)
Pesantren (Islamic Boarding School, henceforth pesantren) and madrasah (Islamic Regular School, henceforth madrasah) have produced thousands and even millions of alumni scattered across the country and even from different foreign countries. In the development of these Islamic schools, they have experienced ups and downs reforms in various sectors such as management, curriculum and so on. In this globalization era, IBS and IRS are more attractive to parents because both are able to produce competent graduates in the field of religion also skilled in other scientific fields (Sciences). In addition, the generation born from the womb of Islamic schools generally have higher character or values of noble character. For example; courteous, polite, obedient to parents and teachers, independent, solidarity, sincerity, tawadhu', simple, egalitarian, and able to work with all parties. The educational values are somewhat hard to come out of school or formal educational institutions.